BUKU KIA DALAM MASA PANDEMI COVID-19 - Rizki Amalia (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2021)
Midwives as the front line in maintaining the health of mothers and children in the midst of the covid-19 pandemic, are a challenge for midwives to improve the quality of midwifery services. Efforts to improve maternal health services during the Covid-19 pandemic in the New Normal Era. Various efforts from the Lamongan district government have been optimal regarding the mapping of hospitals/Puskesmas that handle cases of pregnant women, maternity and postpartum but this does not reduce the fear related to visits to hospitals/Puskesmas they are more comfortable coming to first-level health facilities but there is also a potential health center level the risk of exposure is quite high. So the proposer intends to provide socialization regarding the MCH Handbook as a friend of the mother and child so that the mother and child are calm and comfortable with self-screening and media consultations that make clients not often in contact with health facilities if the illness is not too severe even if they have to make visits, everything is planned. there is no queue at the clinic, of course also preparing everything in sterile conditions and applying all health protocols.